Interaction of multidrug-resistant hypervirulent Klebsiella pneumoniae with components of human innate host defense - Frank R. DeLeo; Adeline R. Porter; Scott D. Kobayashi; Brett Freedman; Mingju Hao; Jianping Jiang; Yi-Tsung Lin; Barry N. Kreiswirth; Liang Chen (mBio, 2023)
ABSTRACT Klebsiella pneumoniae is an important cause of healthcare-associated infections worldwide. This opportunistic pathogen, known as classical K. pneumoniae (cKp), typically causes infections in individuals with comorbidities. cKp is often multidrug resistant, and treatment options are limited. By comparison, hypervirulent K. pneumoniae (hvKp) can cause infections in healthy individuals outside of the healthcare setting. Notably, there has been emergence of strains containing both multidrug resistance and hypervirulence genotypes (MDR hvKp). Whether these strains can circumvent killing by components of the innate immune system remains incompletely determined. Here, we compared the ability of selected hvKp (ST23 and ST86) and MDR hvKp (ST11 and ST147) clinical isolates to survive in human blood and serum and tested phagocytic killing of the microbes by human neutrophils. On average, the hvKp isolates tested had greater survival in blood and serum compared with MDR hvKp isolates. Compared with MDR hvKp isolates, the hvKp isolates had less surface-bound serum complement following culture in normal serum. Consistent with these findings, the percentage of neutrophils with phagocytosed hvKp isolates was limited (<5%), whereas >67% of neutrophils contained ingested MDR hvKp. Phagocytosis of the MDR hvKp isolates was accompanied by significant bacterial killing (P < 0.05). The inability of neutrophils to ingest and kill these hvKp isolates was, in part, overcome by addition of rabbit antiserum specific for these clinical isolates. The results provide insight into host defense against emerging MDR hvKp and are an initial step toward assessing the potential of a vaccine or immunotherapy approach for treatment of infections. IMPORTANCE Klebsiella pneumoniae strains with a combination of multidrug resistance and hypervirulence genotypes (MDR hvKp) have emerged as a cause of human infections. The ability of these microbes to avoid killing by the innate immune system remains to be tested fully. To that end, we compared the ability of a global collection of hvKp and MDR hvKp clinical isolates to survive in human blood and resist phagocytic killing by human neutrophils. The two MDR hvKp clinical isolates tested (ST11 and ST147) were killed in human blood and by human neutrophils in vitro, whereas phagocytic killing of hvKp clinical isolates (ST23 and ST86) required specific antisera. Although the data were varied and often isolate specific, they are an important first step toward gaining an enhanced understanding of host defense against MDR hvKp.